Practicum Learning Techniques in Brassica chinensis Pesticide Contamination Test on UISU FKIP Biology Students 2018-2019 - Fefiani, Yusri (International Journal for Educational and Vocational Studies, 2019)
The research test was carried out at the Biology Laboratory FKIP UISU. The study design used was a Completely Randomized Design (CRD) with 3 treatment tests and five replications, as a comparison of each treatment test used control.This study aims to determine the content of pesticides in Brassica chinensis in Medan city markets, whether pesticides are contaminated or not, and to determine student learning outcomes in biochemical subjects in additives and contaminants in food.In this study, the mortality of C. binotalis larvae was observed in each treatment test, starting from observations on Brassica chinensis leaf samples taken from control, then on Brassica chinensis leaf samples taken from Sambas market, Simpang Limun market, Halat market, and market Like Crowded. Observations were made at 6, 12, 24, 48, and 72 hours after application. The area of leaf damage was observed after 72 hours of application in each treatment test. Likewise, larval weight gain was calculated after 72 hours of application.After 72 hours of treatment test, the highest larval mortality occurred in Brassica chinensis samples taken from the crowded market at 6.22%, with the lowest larval weight gain of 570 mg, and with the least area of leaf damage that was 1,169 mm2. While the lowest larval mortality after 72 hours of treatment test occurred in Brassica chinensis samples taken from the control at 0.89%, with the highest larval weight gain of 588.8 mg, and with the most extensive leaf damage area of 5,486.3 mm2.Before conducting biochemical learning on material additives and contaminants in food to students, a pre-test was made to students, and the average value of student learning outcomes during the pre-test was 60.26 with a standard deviation of 10.09. Whereas after the learning material has been submitted and conducted a post test the average value of student learning outcomes has increased by 74.85 with a standard deviation of 6.25.